High-Dose Vitamin D-Mediated Hypercalcemia as a Potential Risk Factor in Central Nervous System Demyelinating Disease - Häusler, Darius; Torke, Sebastian; Weber, Martin S. (Frontiers in Immunology, 2020)
The exact cause of multiple sclerosis (MS) is unknown; however, it is considered to be an inflammatory disease of the central nervous system (CNS) triggered by a combination of both environmental and genetic factors. Vitamin D deficiency is also discussed as a possible disease-promoting factor in MS, as low vitamin D status is associated with increased formation of CNS lesions, elevated number of relapses and accelerated disease progression. However, it remains unclear whether this association is causal and related and most importantly, whether vitamin D supplementation in MS is of direct therapeutic benefit. Recently, we could show that in a murine model of MS, administration of a moderate vitamin D dose was of clinical benefit, while excessive vitamin D supplementation had a negative effect on disease severity. Of note, disease exacerbation was associated with high-dose vitamin D caused secondary hypercalcemia. Mechanistically dissecting this outcome, we found that hypercalcemia independent of vitamin D similarly triggered activation of disease-perpetuating T cells. These findings caution that vitamin D should be supplemented in a controlled and moderate manner in patients with MS and concomitantly highlight calcium as a novel potential MS risk factor by itself. In this review, we will summarize the current evidence from animal and clinical studies aiming to assess whether vitamin D may be of benefit in patients with MS. Furthermore, we will discuss any possible secondary effects of vitamin D with a particular focus on the role of calcium on immune cells and in the pathogenesis of CNS demyelinating disease.